THU0309 UNILATERAL TEMPORAL ARTERY BIOPSY IS SUFFICIENT FOR DIAGNOSING GIANT CELL ARTERITIS IF THE SERUM C-REACTIVE PROTEIN LEVEL IS 10 MG/DL OR HIGHER. (2nd June 2020) - Kise, T.; Takamasu, E.; Miyoshi, Y.; Yokogawa, N.; Shimada, K.
Abstract : Background: Temporal artery biopsy (TAB) is the gold standard for diagnosing giant cell arteritis (GCA). However, previous studies have reported that the discordance rate of TAB is 3-45%, i.e., in unliteral TAB, GCA may be overlooked in one in five patients, approximately. Evidence as to whether bilateral TAB should be performed initially or one-sided TAB is sufficient for diagnosing GCA is lacking. Objectives: To investigate the predictors of patients with GCA in whom one-sided TAB is sufficient. Methods: The present study was a cross-sectional, single center study conducted from April 1, 2011 to July 31, 2019 at Tokyo Metropolitan Tama Medical Center. Of all consecutive GCA cases for which bilateral TAB was performed, bilaterally positive cases and unilaterally positive cases were extracted as bilateral positive group (BPG) and unilateral positive group (UPG), respectively. GCA was defined in accordance with the classification criteria of the 1990 American College of Rheumatology, and GCA was diagnosed if no other etiology was found within six months after beginning of high-dose glucocorticoid treatment. Demographic, clinical and laboratory data were obtained from the medical records, and the BPG and the UPG were compared statistically in each variable. Statistical significance was defined as p < 0.05. Results: During study, 264 biopsies were performed for 145 cases, who suspected GCA and underwent TAB. The pathological positivity rate was 26.1% (68 / 264 biopsies). Of these, 53 cases had final diagnosis of GCA, in which 43 cases were biopsy proven GCA. Thirty-seven biopsy proven GCA with bilateral TAB were enrolled; 64.9% women; mean (SD) age 75 (8.9) years; median [IQR] TAB length 17.5 [13.0, 20.0] mm; headache 54.1%; jaw claudication 45.9%; scalp tenderness 16.2%; temporal artery (TA) tenderness 32.4%; TA engorgement 32.4%; TA pulse abnormality 5.4%; visual symptoms 2.7%; a fever of 38.5°C or higher 40.5%; shoulder girdle pain 48.6%; imaging of aortitis or arteritis 40.5%; median [IQR] white blood cell 9, 100 [7200, 12050] /μl; median [IQR] platelet cell 37.5 [27.0, 46.3] ×10 4 /μl; median [IQR] C-reactive protein (CRP) 10.1 [3.9, 16.5] mg/dL; erythrocyte sedimentation rate [IQR] 105 [66, 129] mm/h. Thirty-one in 37 cases were positive bilaterally while 6 in 37 cases were positive unilaterally; and the discordance rate was 16.2%. The median sample length after formalin fixation was 19.0 mm for the BPG and 14.5 mm for the UPG ( p = 0.171). The parameters above were compared between UPG and BPG. Of these, only the serum CRP value (mg/dL) differed statistically between groups, and the median value of the two groups was 10.6 and 6.5, respectively (median test: p = 0.031). To predict BPG, in whom unilateral TAB is sufficient for diagnosing GCA, the cut-off value of serum CRP with a specificity of 100% and a sensitivity of 61.3% was set at 9.3 mg/dL (ROC analysis: AUC 0.726). Conclusion: When the serum CRP level is 10 mg/dL or higher in GCA suspected patients, an unilateral TAB alone was sufficient for an accurate diagnosis. References: [1]Hellmich, B, et al. Ann Rheum Dis 2020;79(1):19-30. [2]Breuer, GS, et al. J Rheumatol . 2009;36(4):794-796. [3]Czyz CN, et al. Vascular 2019;27(4):347-351. [4]Durling B, et al. Can J Ophthalmol 2014;49(2):157-161. Disclosure of Interests: None declared